Preparation method and application of dust-free plaster

By optimizing the formula and process of plaster plaster, using automated spraying and particle size monitoring technology, combined with antioxidant steel fibers and glass microbeads, the problems of dust flying, poor uniformity and insufficient mechanical properties of traditional plaster plaster are solved, and efficient, environmentally friendly and healthy construction results are achieved.

CN119751114APending Publication Date: 2025-04-04HEBEI JIANGGONG NEW BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411968669.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the construction process, traditional plaster plaster is dusty, poor mixing uniformity, insufficient mechanical properties and poor environmental protection performance, making it difficult to meet the needs of modern buildings for efficiency, greenness and health.

Method used

Through optimized formulation design and process improvement, an automated spraying device is used to spray white oil evenly, combining particle size monitoring device and precision mixing technology to ensure the uniformity of materials and construction performance. At the same time, steel fibers, glass microbeads and quartz sand are added to optimize the strength, crack resistance and durability of the material.

Benefits of technology

It significantly reduces dust emissions, improves the construction and environmental protection performance of the materials, ensures the uniformity and mechanical properties of the materials, and meets the needs of modern buildings for high efficiency, greenness and health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751114A_ABST
    Figure CN119751114A_ABST
Patent Text Reader

Abstract

The present invention relates to the field of building materials, and discloses a preparation method and application of dust-free plastering gypsum. By carefully adjusting the formula, the present invention mixes raw materials such as β-semihydrate gypsum powder, quartz sand, glass beads, polyvinyl alcohol, cellulose ether in a specific proportion, and incorporates steel fibers treated with antioxidants and food-grade white oil, thereby significantly enhancing the material's anti-cracking performance, dustproof effect, and fluidity during construction. An automated spraying device is used to evenly spray white oil at a constant speed, and a particle size monitoring device is used to dynamically adjust the mixing parameters to ensure the fineness and uniform distribution of material particles. The invention effectively reduces dust emissions by more than 90%, the construction process is smooth, has a high bonding strength, and is suitable for mechanical spraying construction. In addition, the material is environmentally friendly and non-toxic, meeting the needs of modern green buildings for efficient construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a preparation method and application of dust-free plaster gypsum. Background Art

[0002] Plastering gypsum is a key material used for wall leveling and decoration in construction, and its performance directly affects the quality and efficiency of construction. Traditional plastering gypsum is mainly composed of β-hemihydrate gypsum, usually with sand and a small amount of binder to improve strength and construction performance. However, during the mixing and construction process, plastering gypsum is prone to produce a large amount of dust, which not only pollutes the construction environment, but also poses a potential threat to the health of construction workers. Especially when constructing in an indoor environment, the spread of dust is more significant, and long-term exposure may cause pneumoconiosis and other respiratory diseases.

[0003] In order to alleviate the dust problem, the prior art has attempted to add surfactants to the formula to reduce dust flying. However, since surfactants can only partially suppress dust by reducing the surface tension of the particles, their scope of action is relatively limited, and when the proportion of additives is too high, it may lead to a decrease in material performance, such as reduced bonding strength, poor construction fluidity, etc. In addition, the addition of surfactants often brings new chemical residue risks, and is not suitable for scenarios with high requirements for environmental protection and construction health. It can be seen that the prior art has failed to fundamentally solve the dust problem of plaster gypsum, especially in terms of construction efficiency and environmental performance.

[0004] In terms of improving construction performance, traditional plastering gypsum formulas usually enhance the crack resistance and strength of the material by adding sand or steel fibers. However, due to the uneven shape and particle size distribution of the sand particles, coarse particles are easily formed during mixing. These particles not only affect the uniformity of the material, but may also cause an uneven coating surface. In addition, the dispersion of steel fibers in the material is poor, and the fibers with untreated surfaces are prone to oxidation in a humid environment, resulting in a decrease in mechanical properties and even cracking hazards. Therefore, although the adjustment of the existing formula can enhance the mechanical properties of plastering gypsum to a certain extent, it is often accompanied by other defects, and it is difficult to take into account the uniformity, crack resistance and smoothness of construction.

[0005] In construction applications, modern buildings are increasingly using mechanical spraying construction methods to improve efficiency. However, due to the lack of fluidity, traditional plaster often causes equipment blockage and uneven spraying during the spraying process. This phenomenon is mainly attributed to the lack of lubricity and fluidity of the particles in the material formula. The friction between the particles increases under the spraying pressure, resulting in excessive equipment load and even construction interruption. Although the prior art attempts to improve fluidity by adding lubricants, the lubricants used are mostly ordinary industrial-grade products with complex chemical compositions. They are prone to release harmful volatile organic compounds (VOCs) during the spraying process, causing environmental pollution and threatening the health of construction workers. This makes it difficult for traditional formulas to meet the dual needs of modern buildings for environmental protection and efficient construction.

[0006] In addition, with increasingly stringent environmental regulations and enhanced public health awareness, the building materials industry has gradually increased its demand for green and environmentally friendly products. Traditional plastering gypsum has been unable to meet the market demand under the new situation due to its high dust, high risk of chemical residues and insufficient environmental performance. Especially in modern green building projects, higher requirements are placed on low dust, low VOC release and high construction efficiency of materials, and the improvement measures of existing technologies have not yet achieved the desired results.

[0007] Therefore, the present invention provides a preparation method and application of dust-free plastering gypsum to solve the deficiencies of the prior art. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a preparation method and application of dust-free plastering gypsum, aiming to solve the problems of dust flying, poor mixing uniformity, insufficient mechanical properties and poor environmental protection of traditional plastering gypsum during construction. The present invention significantly improves the construction performance, environmental protection performance and service life of the material by optimizing the formula design and process improvement, meeting the requirements of modern construction for high efficiency, greenness and health.

[0009] To achieve the above object, the present invention is implemented by the following technical scheme: a preparation method of dust-free plastering gypsum, comprising the following steps: S1. Mix the following raw materials by weight: Steel fiber: 0.2-0.5 parts; β-hemihydrate gypsum powder: 70-90 parts; Quartz sand: 8-15 parts; Glass beads: 4-8 parts; Polyvinyl alcohol: 0.4-1 part; Gypsum retarder: 0.1-0.3 parts; Portland cement: 2-3.5 parts; Cellulose ether: 0.2-0.5 parts; White oil: 0.6-1.2 parts; Steel Fiber: Enhances the crack resistance of the plaster while increasing the mechanical strength of the material, helping to enhance the overall durability after construction.

[0010] β-hemihydrate gypsum powder: As the main cementitious material, it reacts with water to form dihydrate gypsum, providing basic bonding and hardening properties.

[0011] Quartz sand: acts as aggregate, increases the volume stability and compressive strength of the material, while optimizing the bonding effect and construction feel.

[0012] Glass beads: Improve the workability of plaster and significantly reduce the density of the material through their low density and excellent fluidity.

[0013] Polyvinyl alcohol: Provides adhesion reinforcement, improves the material's flexibility and crack resistance, and helps to evenly disperse the other components.

[0014] Gypsum retarder: Delays the setting time of gypsum, giving the material a longer operating window to adapt to on-site construction needs.

[0015] Portland Cement: Provides additional strength and water resistance, making the finished material suitable for a wider range of use scenarios.

[0016] Cellulose ether: Enhances water retention of plaster materials, optimizes construction fluidity and prevents cracking.

[0017] White oil: As a lubricant and dust suppressant, it improves the construction environment by reducing dust flying, and also plays a wetting and dispersing role to ensure that all ingredients are fully mixed.

[0018] S2. Spray the white oil evenly into the mixer at a constant spraying rate within 200-400 seconds through an automatic spraying device; spray the white oil evenly into the mixer at a constant rate through an automatic spraying device to ensure the uniform distribution of the lubricant, effectively reduce the friction and adhesion of each component during the mixing process, and reduce the generation of dust.

[0019] Precise control of the spraying speed avoids excess or deficiency of white oil to ensure a balance between lubrication effect and material properties.

[0020] This process, combined with automated equipment and precision flow controllers, allows real-time adjustments to further improve mix uniformity and finished product quality.

[0021] S3. Stir in the following order: Stir at low speed for 30-60 seconds at first; Then stir at high speed for 30-90 seconds until the mixture is evenly mixed to obtain dust-free plaster; Low-speed stirring: Preliminary mixing of raw materials to reduce the aggregation of large particles and ensure that the white oil can fully penetrate the surface of gypsum powder, sand and other ingredients to prevent agglomeration.

[0022] High-speed mixing: Enhances mixing uniformity and evenly distributes glass beads and quartz sand in the gypsum matrix through higher shear force, thereby optimizing material properties.

[0023] Combining different stirring speed stages can effectively improve the overall dispersion and uniformity of the material, while avoiding excessive heat accumulation caused by long-term high-speed stirring, which affects material properties.

[0024] S4. Remove particles larger than 300 μm through screening equipment to obtain finished products.

[0025] The screening process can remove oversized particles or inadequately mixed components to ensure a uniform particle size distribution of the finished material and avoid affecting construction performance and surface smoothness due to oversized particles.

[0026] The diameter of the vibrating screen is controlled within 300μm to ensure that the plastering material has suitable particle fineness and construction fluidity, while improving the fineness of the final construction effect.

[0027] Preferably, the interior of the mixer includes: Automatic spraying device: used to evenly spray white oil.

[0028] The automatic spraying device can evenly spray the white oil into the mixture in the mixing chamber in the form of atomization. Through the automatic control system, the spraying rate is precisely adjusted between 0.02-0.05 parts per second, so that the white oil can effectively cover the surface of particles such as gypsum powder, glass beads, and quartz sand.

[0029] The atomized spraying of white oil not only significantly reduces the flying of dust, but also reduces the friction between particles and improves the mixing uniformity. At the same time, the precise spraying rate avoids insufficient or excessive white oil usage affecting the subsequent material performance.

[0030] Particle size monitoring device: used to detect the particle size of the mixture in real time.

[0031] Through laser particle size analysis technology, the particle size monitoring device is embedded in the mixing chamber to measure the particle size distribution of the mixture in real time. When the particles are larger than 300μm, the system will trigger an alarm and automatically extend the mixing time or adjust the mixing parameters.

[0032] The particle size monitoring device ensures the fineness and uniformity of the mixture, avoiding the influence of large particles on the fluidity and surface smoothness of the material during construction. At the same time, real-time detection reduces manual intervention and improves mixing efficiency.

[0033] Temperature control device: used to control the temperature during mixing not to exceed 45°C.

[0034] The temperature control device monitors the temperature of the material in the chamber in real time through a built-in thermal resistor sensor (such as PT100). The jacket coolant or air flow cooling system dynamically adjusts the flow rate according to the temperature control signal to maintain the temperature of the mixing chamber between 20-45°C.

[0035] Controlling the temperature not to exceed 45°C can effectively prevent the gypsum from solidifying prematurely due to excessive temperature, thereby ensuring the operating time and fluidity of the material, while improving the stability of the entire process.

[0036] Preferably, the white oil is food grade mineral oil, and its kinematic viscosity is 30-50 mm at 40 degrees Celsius. 2 / s range.

[0037] Food-grade white oil is environmentally friendly and non-toxic, meeting the environmental protection requirements of building materials and avoiding potential health hazards to construction workers. At the same time, its kinematic viscosity at 40°C is controlled at 30-50mm 2 / s, ensuring that it has good fluidity and lubrication properties, can cover all particle surfaces and improve mixing efficiency.

[0038] Preferably, the spraying rate of the white oil is 0.02-0.05 parts per second, and the spraying accuracy is controlled by a precision flow controller.

[0039] White oil is sprayed at a rate of 0.02-0.05 parts per second and adjusted by a precision flow controller to ensure that the white oil is evenly distributed during the mixing process. Excessive spraying will not increase costs or affect the performance of the finished product, and insufficient spraying will not reduce the dust control effect.

[0040] Preferably, the steel fiber has a length of 3 mm, a diameter of 50-150 μm, and is treated with an anti-oxidation coating on the surface.

[0041] The steel fiber has a length of 3mm and a diameter of 50-150μm, and can be evenly dispersed in the plaster, playing a role in enhancing the material's crack resistance while improving its overall strength and tensile properties.

[0042] The surface anti-oxidation coating can effectively prevent the steel fiber from oxidative corrosion in a humid environment and improve the durability of the material.

[0043] Preferably, in the step S3, after the mixing is completed, the mixture is cooled to room temperature and then screened, and the cooling method is cooling by circulating coolant or air flow through the jacket, and the screening equipment is a vibrating screen with a mesh diameter of 300 μm.

[0044] After mixing, the mixture is cooled to room temperature through a jacket circulating coolant or air flow cooling system to prevent residual heat from causing gypsum hardening or performance degradation.

[0045] The vibrating screen removes oversized particles or inadequately mixed components through a 300 μm sieve hole to ensure the fineness and uniformity of the material, thereby improving the construction performance and surface finish of the finished product. Preferably, the particle size range of the glass microbeads is 5-150 μm, and the compressive strength thereof is not less than 10 MPa, the particle shape of the quartz sand is round or sub-round, and the silicon content thereof is not less than 95%.

[0046] The low-density characteristics of glass beads can reduce the overall density of plaster and improve the portability of construction; its particle size is controlled in the range of 5-150μm, and can be evenly distributed in the matrix to optimize the strength and fluidity of the material; the compressive strength is not less than 10MPa, ensuring that it will not be crushed during construction and use.

[0047] Round or sub-round particles can reduce internal friction, improve mixing uniformity and construction smoothness; up to 95% silicon content provides the material with good stability and resistance to chemical corrosion.

[0048] Preferably, a dust-free plastering gypsum is used in building plastering construction, and the dust-free plastering gypsum is suitable for mechanical spraying construction with a construction thickness of 5-20 mm.

[0049] The present invention provides a preparation method and application of dust-free plastering gypsum, which has the following beneficial effects: 1. The present invention adopts a technical solution of spraying white oil at a uniform speed through an automated spraying device, so that the white oil is evenly distributed on the surface of all raw materials during the mixing process to form a dust-proof layer. The technical effect of significantly reducing dust emissions during mixing and construction is achieved. Compared with the solution of simply adding surfactants to suppress dust in the prior art, the problem of limited dust control effect is solved, while avoiding the hidden danger of chemical residue risk.

[0050] 2. The present invention realizes real-time detection and adjustment of the particle size of the mixture by integrating a particle size monitoring device in the mixer and combining the technical solution of dynamically controlling the mixing time. The technical effect of improving the mixing uniformity and ensuring the stability of the material particle size distribution is achieved. Compared with the solution in the prior art that relies on a fixed stirring time, the present invention effectively solves the problem of coarse particle residue affecting the smoothness of material construction, and further ensures the construction adaptability and stability of the material.

[0051] 3. The present invention optimizes the formula and adds steel fibers that have been treated with antioxidants, and combines the scientific ratio of glass beads and quartz sand to greatly improve the strength, crack resistance and durability of plaster. Steel fibers provide good tensile properties, glass beads improve construction fluidity, and quartz sand enhances the structural strength of the material. The technical effect of taking into account both construction performance and mechanical properties is achieved. Compared with the existing practice of only improving strength through a single aggregate, the problem of easy cracking and insufficient strength of the material is overcome.

[0052] 4. By using food-grade white oil as a lubricant and dust-proof agent, and combining it with the optimized design of high-efficiency mechanical spraying construction, the present invention not only improves the construction efficiency, but also realizes a healthy and environmentally friendly construction environment. The technical effect of reducing the residue of chemical additives and harmful substances is achieved. Compared with the practice of using industrial lubricants or chemical modifiers in the prior art, the present invention effectively solves the health risks that may exist in the construction process and finished products, and at the same time promotes the development of the building materials industry towards green and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 The present invention is a flow chart of a method for preparing dust-free plastering gypsum. DETAILED DESCRIPTION

[0054] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] Please refer to the attached Figure 1 : Example 1 Ingredients Add the raw materials into the mixer in the following weight ratio: Steel fiber: 0.3 parts; β-hemihydrate gypsum powder: 85 parts; Quartz sand: 12 parts; Glass beads: 6 parts; Polyvinyl alcohol: 0.8 parts; Gypsum retarder: 0.2 parts; Portland cement: 3 parts; Cellulose ether: 0.3 parts; White oil: 1 part.

[0056] Mixing process Mixing equipment: Use PerMixPTS series horizontal twin-shaft paddle mixer with a capacity of 500 liters and a twin-shaft paddle stirring system.

[0057] Automatic spraying device: Use Dürr EcoGun 246 spraying device to spray white oil into the mixture at a rate of 0.04 parts / second at a constant speed for 300 seconds.

[0058] Start the mixer at low speed (40 rpm), initially mix the materials for 30 seconds, then start the spraying device while maintaining the stirring state. After the white oil spraying is completed, increase the mixer speed to 120 rpm and stir at high speed for 60 seconds.

[0059] Detection and screening Particle size monitoring device: equipped with Malvern Mastersizer 3000 particle size analyzer, which automatically stops stirring when it detects that the proportion of particles with a particle size greater than 300 μm is less than 1%.

[0060] Cooling device: Use a jacket circulation cooling system (coolant flow rate is 1.5L / min) to cool the mixture to room temperature.

[0061] Screening equipment: Russell Compact Sieve series vibrating screen with a screen hole diameter of 300 μm is used to screen the mixture to obtain the finished plaster.

[0062] Example 2 Ingredients Put the following raw materials by weight into the mixer: Steel fiber: 0.4 parts; β-hemihydrate gypsum powder: 90 parts; Quartz sand: 10 parts; Glass beads: 5 parts; Polyvinyl alcohol: 0.5 parts; Gypsum retarder: 0.15 parts; Portland cement: 2.5 parts; Cellulose ether: 0.2 parts; White oil: 0.8 parts.

[0063] Mixing process Mixing equipment: Use INOXPA mixing equipment MH series, equipped with intelligent control system.

[0064] Automatic spraying device: GracoProXp85 spray system was selected, and the white oil spraying rate was 0.03 parts / second for 350 seconds.

[0065] Start the mixer at a low speed (35 rpm) and spray the white oil at the same time. After spraying, increase the stirring speed to 100 rpm and stir for 90 seconds.

[0066] Cooling and screening Cooling system: Using GEA cooling modules, the mixture is cooled to room temperature (about 25°C) by air flow cooling.

[0067] Screening equipment: Sweco Vibro-Energy separation screen with a sieve hole diameter of 300 μm was used for screening.

[0068] Example 3 Ingredients Add the following raw materials into the mixer in proportion: Steel fiber: 0.5 parts; β-hemihydrate gypsum powder: 80 parts; Quartz sand: 15 parts; Glass beads: 7 parts; Polyvinyl alcohol: 0.7 parts; Gypsum retarder: 0.3 parts; Portland cement: 3.5 parts; Cellulose ether: 0.4 parts; White oil: 1.2 parts.

[0069] Mixing process and mixing equipment: Mixer (W300 model) equipped with a twin-shaft blade agitator and an online detection system.

[0070] Automatic spraying device: Use Binks AG363 atomizing sprayer, the spraying rate is 0.05 parts / second, and the spraying time is 400 seconds.

[0071] While stirring at low speed (50 rpm), evenly spray the white oil. Then switch to high speed mode (120 rpm) and stir at high speed for 60 seconds to ensure that the materials are fully mixed.

[0072] Cooling and screening temperature control system: Use JULABO circulating cooler to monitor and adjust the mixing temperature in real time to ensure that the temperature is maintained below 40°C.

[0073] Screening equipment: VibraScreenerDynamicScreener is used to screen particles with a size greater than 300μm.

[0074] Example 4 Ingredients Add the raw materials into the mixer in the following proportions: Steel fiber: 0.2 parts; β-hemihydrate gypsum powder: 85 parts; Quartz sand: 10 parts; Glass beads: 6 parts; Polyvinyl alcohol: 0.6 parts; Gypsum retarder: 0.25 parts; Portland cement: 3 parts; Cellulose ether: 0.3 parts; Food grade white oil: 0.8 parts.

[0075] Mixing process Mixing equipment: Use YSTRALConti-TDS mixing equipment, combined with automatic feeding function.

[0076] Automatic spraying device: equipped with SATAjet5000BHVLP spray gun, with a spraying rate of 0.02 parts / second and a spraying time of 300 seconds.

[0077] The mixture was stirred at low speed (40 rpm) for 40 seconds while spraying with white oil, followed by stirring at high speed (100 rpm) for 70 seconds.

[0078] Screening and cooling Cooling system: Use HaskrisR100 cooling module to cool the mixture to 25℃ by circulating coolant.

[0079] Screening equipment: Kason Vibroscreen circular vibrating screen with a sieve hole diameter of 300 μm is used to ensure uniform particle size of the finished product.

[0080] Comparative Example: Comparative Example 1 Ingredients: Add the raw materials in the mixer according to the ratio of Example 1, as follows: Steel fiber: 0.3 parts; β-hemihydrate gypsum powder: 85 parts; Quartz sand: 12 parts; Glass beads: 6 parts; Polyvinyl alcohol: 0.8 parts; Gypsum retarder: 0.2 parts; Portland cement: 3 parts; Cellulose ether: 0.3 parts; White oil: 1 part.

[0081] Mixing process: Mixing equipment: The same PerMix PTS series mixer as in Example 1 was used.

[0082] Spraying device: A simple nozzle device was used instead of the Dürr EcoGun 246 spraying device, which could not achieve precise flow control. The white oil was sprayed into the mixing chamber by manual adjustment. The spraying time was 350 seconds, but due to insufficient spraying accuracy, the spraying amount fluctuated.

[0083] Start the mixer and stir at low speed (40 rpm) for 30 seconds, and spray white oil at the same time. After spraying white oil, directly increase the stirring speed to 120 rpm and stir at high speed for 60 seconds. No particle size monitoring equipment is used to adjust the particle size.

[0084] Cooling and sieving: Cooling device: Uses ordinary fans for simple airflow cooling, cannot monitor temperature in real time, and causes uneven cooling.

[0085] Screening: Screen through a vibrating screen with a mesh diameter of 300 μm.

[0086] Comparative Example 2 Ingredients: The raw materials are the same as in Example 2: Steel fiber: 0.4 parts; β-hemihydrate gypsum powder: 90 parts; Quartz sand: 10 parts; Glass beads: 5 parts; Polyvinyl alcohol: 0.5 parts; Gypsum retarder: 0.15 parts; Portland cement: 2.5 parts; Cellulose ether: 0.2 parts; White oil: 0.8 parts.

[0087] Mixing process: Mixing equipment: INOXPA mixing and stirring equipment MH series is used, which is the same as in Example 2.

[0088] Spraying device: Use GracoProXp85 spray system, spray rate is 0.03 parts / second, spray time is 350 seconds.

[0089] Stirring: Start the mixer at low speed (35 rpm). After spraying the white oil, increase the speed to 100 rpm and stir at high speed for 90 seconds.

[0090] There is no Malvern Mastersizer 3000 particle size analyzer or real-time particle size monitoring equipment. The mixing time is completely fixed (no feedback adjustment), and there is no adjustment measure even if the particle size exceeds the standard.

[0091] Cooling and sieving: The cooling and screening process is the same as in Example 2, but due to the lack of monitoring of the particle size, the mixing quality cannot be guaranteed.

[0092] Comparative Example 3 Ingredients: The proportion of steel fiber is adjusted to 0.8 parts, and the proportions of other materials are the same as those in Example 3: β-hemihydrate gypsum powder: 80 parts; Quartz sand: 15 parts; Glass beads: 7 parts; Polyvinyl alcohol: 0.7 parts; Gypsum retarder: 0.3 parts; Portland cement: 3.5 parts; Cellulose ether: 0.4 parts; White oil: 1.2 parts.

[0093] Mixing process: Mixing equipment: using The mixer (W300 model) is the same as that in Example 3.

[0094] The steel fiber is not subjected to surface anti-oxidation treatment and is made of ordinary raw materials.

[0095] Spraying device: Use Binks AG363 sprayer, the spraying rate is 0.05 parts / second, and the spraying time is 400 seconds.

[0096] Stirring parameters: low speed stirring for 50 seconds, followed by high speed stirring (120 rpm) for 60 seconds.

[0097] Cooling and sieving: The cooling device and screening equipment are the same as those in Example 3.

[0098] Comparative Example 4 Technical solution for replacing food grade white oil with common lubricants Ingredients: The food-grade white oil was replaced with industrial-grade mineral oil, and the rest of the formula was the same as in Example 4: Steel fiber: 0.2 parts; β-hemihydrate gypsum powder: 85 parts; Quartz sand: 10 parts; Glass beads: 6 parts; Polyvinyl alcohol: 0.6 parts; Gypsum retarder: 0.25 parts; Portland cement: 3 parts; Cellulose ether: 0.3 parts; Industrial grade mineral oil: 0.8 parts.

[0099] Mixing process: Mixing equipment: YSTRAL Conti-TDS mixing equipment is used, which is the same as in Example 4.

[0100] Spraying device: Use SATAjet5000BHVLP spray gun, spray rate is 0.02 parts / second, spray time is 300 seconds.

[0101] Stirring parameters: low speed stirring (40 rpm) for 40 seconds, high speed stirring (100 rpm) for 70 seconds after spraying.

[0102] Cooling and sieving: The cooling and screening equipment is the same as in Example 4.

[0103] Comparative Example 5 (corresponding to Example 1) Unreasonable spraying rate plan Ingredients: Add the following into the mixer according to the formula of Example 1: Steel fiber: 0.3 parts; β-hemihydrate gypsum powder: 85 parts; Quartz sand: 12 parts; Glass beads: 6 parts; Polyvinyl alcohol: 0.8 parts; Gypsum retarder: 0.2 parts; Portland cement: 3 parts; Cellulose ether: 0.3 parts; White oil: 1 part.

[0104] Mixing process: Spraying device: Dürr EcoGun 246 was used, but the spraying rate was adjusted to 0.08 parts / second and the spraying time was shortened to 125 seconds, resulting in the spraying process being too fast.

[0105] Mixing parameters: Mix at low speed for 30 seconds, then mix at high speed for 60 seconds after spraying, without additional adjustment.

[0106] Cooling and screening: The cooling and screening steps are the same as in Example 1.

[0107] Test experiment: Experiment 1: Dust emission test Experimental description: The purpose of the experiment is to evaluate the ability of different technical solutions to control dust emissions during the mixing process by comparing Example 1 with Comparative Example 1. The experiment focuses on verifying the difference between the automated precision spraying device and the traditional manual spraying method, and testing the peak and average concentration of dust emissions.

[0108] Experimental steps: Experimental preparation: Use PerMix PTS series horizontal twin-shaft paddle mixer and DustTrak II 8530 dust concentration detector. Place the mixer and detector in a closed laboratory (space size 10m 3 ), turn off the ventilation system to ensure effective measurement of dust concentration.

[0109] Example 1 Test: The raw materials were added to the mixer according to the formulation and process of Example 1. The automatic spraying device Dürr EcoGun 246 was started, the spraying rate was set to 0.04 parts / second, and the spraying duration was 300 seconds.

[0110] Start the DustTrakII8530 and record the dust concentration every second after the mixing starts until the spraying is completed and the mixer stops running.

[0111] Comparative Example 1 Test: The same raw materials were added to the mixer according to the formula and process of Comparative Example 1. A manual nozzle was used instead of the automatic spraying device, the spraying rate was manually adjusted (without precise control), and the spraying time was 350 seconds.

[0112] DustTrakII8530 is also used to record dust concentration data to maintain operational consistency.

[0113] Data processing: Each test was repeated 3 times and the average value was taken. The peak concentration, average concentration and total dust release of dust emission were recorded.

[0114] Experimental data: Dust emission data of Example 1 and Comparative Example 1 The experimental results are clear at a glance. The dust concentration of the embodiment is much lower than that of the comparative example. This is not a coincidence. The automated spraying device precisely atomizes the white oil, and the spraying rate is stable and uniform, which can quickly form a lubricating film on the particle surface. This design effectively suppresses the flying of dust during the mixing process. The traditional manual nozzle sprays unevenly, some particles are not wetted in time, and a large amount of dust is scattered, resulting in a surge in concentration.

[0115] The generation of dust is the result of high-speed collisions between particles inside the mixer, and white oil, as a lubricant, forms a protective barrier between particles. In the embodiment, precise spray rate control allows the lubrication layer to form at just the right time, and the friction and collision strength of the particles are significantly reduced. In the comparative example, the instability of the spray rate causes incomplete lubrication, and a large number of particles fly and spread due to static electricity and airflow effects. The release of this dust not only affects the mixing efficiency, but also poses a potential threat to the health of construction workers.

[0116] The experimental results directly point to the practical application value of the key invention. Precision spraying is not just about reducing dust, it also optimizes the mixing uniformity of raw materials, laying the foundation for subsequent construction fluidity. The reason why the dust concentration data in the comparison is so high is that traditional technology fails to solve the problem of particle distribution control from the source. This gap not only affects the production process, but will also be transmitted to the final construction stage, bringing quality risks.

[0117] Experiment 2: Mixing uniformity test Experimental description: The purpose of this experiment is to evaluate the effect of the particle size monitoring device on mixing uniformity by comparing Example 2 with Comparative Example 2. Mixing uniformity is based on the material particle size distribution as an indicator, and the proportion of particles with a particle size of more than 300 μm is used as a core parameter to judge the fineness and uniformity of the material.

[0118] Experimental steps: Experimental equipment preparation: Mixing equipment: Use INOXPA MH series mixing and stirring equipment to mix according to the formula and process of Example 2 and Comparative Example 2 respectively.

[0119] Particle size detector: Malvern Mastersizer 3000, detection range 0.01-3000 μm, accuracy ±1 μm.

[0120] Sample collection tool: Randomly collect 50g of the mixture from the sampling port in the mixing chamber and put it into a sealed bag for testing.

[0121] Example 2 Test: Mixing was performed according to the process of Example 2. After the mixer was started, the particle size monitoring device monitored the particle size distribution in real time. The mixer speed was gradually adjusted from low speed (35 rpm) to high speed (100 rpm). When the particle size monitoring device detected that the proportion of particles with a particle size greater than 300 μm was less than 1%, stirring was automatically stopped.

[0122] Three samples (50 g each) were randomly taken from the mixing chamber, and the particle size distribution of the samples was measured using a Malvern Mastersizer 3000.

[0123] Comparative Example 2 Test: Mix according to the process of Comparative Example 2, without a particle size monitoring device. The mixing time is fixed at 120 seconds, and the speed is set to a low speed of 35 rpm for stirring for 60 seconds and then switched to a high speed of 100 rpm for stirring for 60 seconds.

[0124] Three samples (50 g each) were randomly taken from the mixing chamber, and the particle size distribution of the samples was measured using a Malvern Mastersizer 3000.

[0125] Data recording and analysis: Detect the proportion of particles with a size greater than 300 μm.

[0126] Each group was tested 3 times, and the average value was taken after recording the results each time.

[0127] Experimental data: Particle size distribution data of Example 2 and Comparative Example 2 The difference in particle size is not a superficial numerical problem, but a core performance of the mixing process. The particle size monitoring device used in the example adjusts the stirring parameters in real time to ensure that large particles are fully broken and dispersed at an early stage. This process allows the particles to be more evenly distributed in the mixing chamber, avoiding the situation where some components aggregate to form coarse particles. The control sample only relies on fixed-time stirring, and the mixing effect depends entirely on luck, and the particle size of some particles exceeds the threshold.

[0128] Looking further, the inside of the mixer is a dynamic high-shear environment. The particle size monitoring device plays an important role in this process, capturing changes in particle size in real time. It is not just a measurement tool, but more like a feedback regulation system. Through its guidance, the mixing equipment can be optimized, and the proportion of coarse particles will naturally drop significantly. The control group without monitoring can only rely on time to complete the mixing, and obviously ignores the problem of uneven particle distribution. Such a gap is not only reflected in the material performance, but also affects the construction performance.

[0129] Uniformity is the core indicator of the quality of plaster construction. If there are large particles larger than 300μm in the material, it will cause blockage or uneven distribution during spraying, and the surface will be rough and uneven. The technology in the embodiment ensures fine particles, smoother construction, uniform spray coverage, and significantly improved surface flatness of the finished product. This performance optimization is not accidental, but the result of the synergy of hybrid technology and real-time monitoring.

[0130] Experiment 3: Mechanical properties test Experimental description: This experiment aims to evaluate the effect of steel fiber ratio and its antioxidant treatment on the crack resistance and compressive strength of plaster by comparing Example 3 with Comparative Example 3. The experiment mainly tests the compressive strength and crack resistance (bending load) of the material, revealing the significant difference in mechanical properties between the formulation and treatment process optimization.

[0131] Experimental steps: Experimental equipment and tools: Compression strength testing machine: Instron 3382, test range 0-50 MPa.

[0132] Crack resistance test: Three-point bending test fixture, used to test the bending bearing capacity of the test block.

[0133] Mould: Steel mould with the size of 40×40×160mm to ensure the consistency of the test block.

[0134] Sample preparation: Prepare plastering gypsum according to the formula of Example 3 and Comparative Example 3 respectively.

[0135] Pour the mixed material into the mold, vibrate to exhaust, let it stand for 24 hours to cure, and cure it for up to 28 days after demoulding to ensure the stability of the mechanical properties test.

[0136] Compressive strength test: The test block was placed in an Instron 3382 compression testing machine, loaded at a speed of 2 mm / min, the compressive failure load of the test block was recorded, and the compressive strength (unit: MPa) was calculated.

[0137] Three test blocks were tested in each group, and the compressive strength of each test block was recorded and the average value was taken.

[0138] Crack resistance test: Using a three-point bending fixture, load the specimen until it breaks and record the bending load (unit: N).

[0139] During the test, the length of crack extension is observed and the crack development characteristics are recorded.

[0140] Three test blocks were tested in each group, and the bending load of each test block was recorded and the average value was taken.

[0141] Experimental data: Mechanical properties data of Example 3 and Comparative Example 3 Improving crack resistance and compressive strength is not as simple as adding more steel fibers. The steel fibers treated with antioxidants are used in the embodiments, which not only provide additional strength support, but also improve the bonding performance between the fibers and the gypsum matrix. In particular, when the fibers are evenly distributed in the matrix, they bear part of the stress transfer when the material is stressed, inhibiting the rapid expansion of cracks. The fibers in the comparative example are not treated, and the bonding strength between the fiber surface and the matrix is ​​poor, so the mechanical properties are naturally difficult to match.

[0142] The core difference in the material's crack resistance can be seen from the length of the crack. The cracks in the example are shorter and evenly distributed, indicating that the fibers inside the material have an effective blocking effect on the cracks and the fracture mode is more moderate. This is similar to the "toughening mechanism" in high-performance materials, where the fibers provide additional resistance when microcracks initiate. The cracks in the control group expand rapidly and increase significantly in length, which means that the matrix lacks effective constraints from the fibers and exhibits typical brittle failure characteristics.

[0143] The improvement of compressive strength not only depends on the contribution of fiber, but also the role of glass beads and quartz sand cannot be ignored. In the embodiment, glass beads enhance the density of the matrix through their tiny particle size, and quartz sand provides stable skeleton support. This multi-component synergy forms a matrix structure with uniform strength. In the comparative example, due to the poor bonding between fiber and matrix, the test block is more prone to local failure during loading, and the compressive strength shows large fluctuations and reductions. These detailed differences in performance are the intuitive embodiment of process and formula optimization.

[0144] Experiment 4: Construction performance test Experimental description: The purpose of the experiment is to evaluate the fluidity, spraying uniformity and bonding strength of the material in mechanical spraying construction by comparing Example 4 with Comparative Example 4. The focus is on verifying the influence of the selection of white oil (food grade and industrial grade) and its effect on construction performance and environmental adaptability.

[0145] Experimental steps: Experimental equipment and tools: Spraying equipment: Wagner ProSpray 3.20 high-pressure airless sprayer, working pressure 15 MPa.

[0146] Bond strength tester: Elcometer 106 pull-off bond tester, with a detection range of 0-10MPa.

[0147] Substrate: Standard concrete slab (size 300×300×30mm), surface polished with sandpaper.

[0148] Spraying fluidity test: The materials of Example 4 and Comparative Example 4 were respectively loaded into the hopper of the spraying machine.

[0149] Under the same pressure (15 MPa), the material was continuously sprayed onto the substrate surface, and the spraying thickness was controlled at 10 mm.

[0150] Record whether blockage, uneven spraying or equipment abnormality occurs during the spraying process, and observe the leveling of the material after spraying.

[0151] Coating bond strength test: After spraying, the samples were cured at room temperature for 7 days.

[0152] The bond strength of the cured coating was tested using a pull-off bond tester. The pull-off head was attached to the coating surface and loaded until the coating was separated from the substrate. The maximum pull-off force (MPa) was recorded.

[0153] The test was repeated 5 times for each group, and the results were recorded and averaged.

[0154] Spraying uniformity assessment: Use a coating thickness detector to randomly detect the coating thickness at 10 points on the substrate surface, calculate the standard deviation of the coating thickness, and evaluate the spraying uniformity.

[0155] Experimental data: Construction performance test data of Example 4 and Comparative Example 4 The spraying process itself is a test, especially in mechanized construction, the fluidity and uniformity of the material determine whether the construction task can be completed efficiently. The food-grade white oil in the embodiment plays a dual role of lubrication and stability, making it easier for particles to pass through the pipeline under the spraying pressure without any blockage. Although the industrial-grade lubricating oil in the comparative example may be more economical in cost, it obviously cannot provide the same effect. Frequent blockages directly slow down the construction efficiency and even affect the overall quality of the spraying.

[0156] From the bonding strength data, the coating in the example is firmly attached to the surface of the concrete slab, indicating that the formula design in the material (such as glass beads and quartz sand) forms a higher interfacial bonding force. However, due to the fluidity of the material, the coating in the comparative example is easily stratified during spraying, and the bonding force with the substrate after curing is obviously insufficient. Such performance not only affects the construction effect, but also increases the risk of peeling and cracking in long-term use, which is obviously unreliable.

[0157] The uniformity of thickness is even more critical, especially in large-scale construction. If the coating thickness fluctuates too much, it will directly lead to material waste and affect the appearance and flatness of the wall. The uniformity in the embodiment benefits from the improvement of the particle wetting effect during the white oil spraying process, and the leveling property is naturally improved. However, the material of the comparative example obviously shows a rough feeling after spraying, the surface particles are unevenly accumulated, and the coating thickness has a large deviation. This problem is not accidental, but is caused by the difference in mechanism between different lubrication schemes.

[0158] Experiment 5: Environmental testing Experimental description: The experiment aims to compare the environmental impact of Example 4 and Comparative Example 4 during the construction process, especially the release of volatile organic compounds (VOCs). The focus is on verifying the difference in environmental performance between food-grade white oil and industrial-grade lubricants, and clarifying whether the construction materials meet the needs of modern environmentally friendly buildings.

[0159] Experimental steps: Experimental equipment and tools: VOC detector: RAE Systems Mini RAE 3000, detection range is 0.1-10,000 ppm, accuracy is ±1 ppm.

[0160] Experimental environment: Closed laboratory, space size 20m 3 , simulate construction scenes to ensure data collection without external interference.

[0161] Spraying equipment: Wagner ProSpray 3.20 sprayer, spraying pressure is 15 MPa.

[0162] Example 4 Test: The material of Example 4 was poured into a sprayer, and the wall was constructed in a closed laboratory according to a standard spraying process. The spraying thickness was 10 mm and the construction time was 10 minutes.

[0163] During the construction period and 10 minutes, 30 minutes and 1 hour after the construction, the VOC concentration in the indoor air was detected using MiniRAE3000 and recorded once at each time point.

[0164] Comparative Example 4 Test: The material of Comparative Example 4 was poured into a sprayer and tested using the same application conditions.

[0165] Also record the VOC concentration data at each time point during and after the construction.

[0166] Data recording and analysis: Each group of experiments was repeated three times, and the change trend of VOC peak and average concentration was recorded.

[0167] Compare the difference in air quality during and after construction to evaluate environmental performance.

[0168] Experimental data: VOC concentration test data of Example 4 and Comparative Example 4 The key to the difference in environmental performance lies in the essential properties of white oil. The food-grade white oil used in the example has extremely low volatility during the construction process, and the VOC concentration is almost negligible, which not only improves the air quality of the construction environment, but also protects the health of the construction workers. The VOC concentration of the industrial-grade lubricant in the comparative example is surprisingly high, with a pungent smell during construction, and even maintaining a high concentration of pollution within 1 hour after the construction is completed, which shows that the volatile components have a long retention time and pose a long-term threat to the environment and health.

[0169] The generation of VOC is mainly due to the volatilization of chemical components in the material under high-pressure spraying and environmental exposure. The selection of food-grade white oil gives the material good environmental protection characteristics. Its chemical structure is relatively stable and the molecular weight distribution is uniform, which greatly reduces the generation of low-molecular volatiles. Industrial-grade lubricants are often mixed with a variety of low-quality ingredients, and a large amount of harmful substances are released during spraying. This is not only reflected in the VOC value, but can also be intuitively perceived through the smell. The difference between the two lies in the gap between material selection standards and environmental awareness.

[0170] From a mechanistic point of view, the rapid reduction of VOC is inseparable from the role of white oil in the mixing process. Food-grade white oil evenly wets the surface of particles during mixing, forming a stable dispersion system, reducing the intense friction between particles and air during spraying. This process design fundamentally reduces the release of volatile components. However, the materials in the comparative example are not mixed evenly, and there is a large amount of exposed industrial lubricants on the surface of the particles. When sprayed, they directly contact the air and evaporate quickly, causing serious environmental pollution problems. This difference is not only a comparison in data, but also a watershed in environmental protection concepts.

[0171] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing dust-free plastering gypsum, characterized in that: The following steps are involved: S1. Mix the following raw materials by weight: Steel fiber: 0.2-0.5 parts; β-hemihydrate gypsum powder: 70-90 parts; Quartz sand: 8-15 parts; Glass beads: 4-8 parts; Polyvinyl alcohol: 0.4-1 part; Gypsum retarder: 0.1-0.3 parts; Portland cement: 2-3.5 parts; Cellulose ether: 0.2-0.5 parts; White oil: 0.6-1.2 parts; S2, spraying the white oil evenly into the mixer at a constant spraying rate within 200-400 seconds through an automatic spraying device; S3. Stir in the following order: Stir at low speed for 30-60 seconds at first; Then stir at high speed for 30-90 seconds until the mixture is evenly mixed to obtain dust-free plaster; S4. Remove particles larger than 300 μm through screening equipment to obtain finished products.

2. The method for preparing dust-free plaster according to claim 1, characterized in that: The interior of the mixer includes: Automatic spraying device for evenly spraying white oil; A particle size monitoring device is used to detect the particle size of the mixture in real time; The temperature control device is used to control the temperature during the mixing process not to exceed 45°C.

3. The method for preparing a dust-free plaster according to claim 1, characterized in that: The white oil is food grade mineral oil, and its kinematic viscosity is 30-50 mm at 40 degrees Celsius. 2 / s range.

4. The preparation method and application of dust-free plaster according to claim 1, characterized in that: The spraying rate of the white oil is 0.02-0.05 parts per second, and the spraying accuracy is controlled by a precision flow controller.

5. The preparation method and application of dust-free plaster according to claim 1, characterized in that: The steel fiber has a length of 3 mm, a diameter of 50-150 μm, and is treated with an anti-oxidation coating on the surface.

6. The method for preparing dust-free plaster according to claim 1, characterized in that: In the step S3, after the mixture is evenly mixed, it is cooled to room temperature and then screened. The cooling method is cooling by circulating coolant or air flow through the jacket. The screening equipment is a vibrating screen with a mesh diameter of 300 μm.

7. The method for preparing dust-free plaster according to claim 1, characterized in that: The particle size of the glass microbeads ranges from 5 to 150 μm, and the compressive strength thereof is not less than 10 MPa. The particle shape of the quartz sand is round or sub-round, and the silicon content thereof is not less than 95%.

8. Application of the dust-free plastering gypsum according to any one of claims 1 to 7 in building plastering construction, characterized in that: The dust-free plaster is suitable for mechanical spraying construction with a construction thickness of 5-20mm.